(untitled) (Journal of Family Sciences, 2017)
Public houses usually are a high density residential which leads to fire hazard, poor emergency services, as well as the highly increased of family vulnerability. This study aims to analyze the potential fire hazard, vulnerability, and subjective wellbeing of families living in the Jatinegara public house. The design of this study was cross sectional involving 157 families whom selected by stratified random sampling. The study found that age of wife and attitude towards the hazard of fire had a positive relationship to subjective wellbeing of the family. Social dimension and economic dimensions of vulnerability had a negative relationship with subjective wellbeing. Results of regression analysis found that age of wife and familiy’s attitudes toward the fire hazard had a positive effect on subjective wellbeing of the family, while the age of husband, income per capita, social vulnerability, and vulnerability of economic had a negative effect on subjective wellbeing of the family.